ANALISIS SISTEM INFORMASI AKUNTANSI ATAS SIKLUS PENGGAJIAN PADA UMKM IL BENGKEL - Roagave L. Toruan; Aprilia Lerrech; Wd. Utami Wardani; Muhamad Alif Syah Ingratubun; Era Sianipar; Bryan Freyl Z. Manihuruk; Dian Ma’ruf; Nathalia Putri Salamahu; Sri Wahyuni Ngabalin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to understand the human resource or payroll cycle procedure and compare the human resource or payroll cycle procedure with the theory of accounting information systems for this human resource or payroll cycle. This research method was conducted using the interview method, because it can provide accurate information about the accounting information system in the human resources section and is able to meet research needs. And the results show that the human resource or payroll cycle has been carried out properly, where the owner includes all departments in the UMKM iL Workshop and it is known that business activities in this business are still implemented manually and have not used more advanced technologies.